п-electron affinity of the nitrogenous bases of nucleic acids - Obernikhina, N.V.; Nikolaev, R.O.; Kachkovsky, O.D.; Tkachuk, Z.Yu. (Reports of the National Academy of Sciences of Ukraine, 2019)
The relative position of the frontier molecular orbitals (MO) of nucleic acid bases is investigated. It allows one to analyze their donor/acceptor properties in more details, and is a fundamental characteristic of conjugated molecules. Non-covalent interaction specify the spatial constitution of the chains of nucleic acids and their physical and chemical properties in the ground and excited states. Aromatic π-π stacking interactions are generally defined as the attractive interactions that occur between the π-clouds of aromatic systems in a parallel, face-to-face orientation, thus, it could be considered as an affinity of the conjugated molecules. They play a fundamental role in many aspects of chemistry and biochemistry, for example, in the fields molecular recognition self-assembly supramolecular chemistry, and general host-guest interactions. π-π-stacking in biology is of the integral to the structure and function of proteins, cofactors and substrates. Although this interaction is comparatively weak, it leads to large effects; so, DNA (deoxyribonucleic acid) structure being can be considered as an essential example. In such case in tricate scenarios, the π-π interaction is considered very often as some sort of “deus ex machine”, intervening in reactions, provides the additional stabilizing of helix complexes, and influencing the structure. Therefore, the energetic and structural features of these interactions can be estimated, which would be extremely useful in the modeling and understanding of many biological important phenomena. For the quantitative quantum-chemical evaluation of the donor-acceptor properties of the purine and pyrimidine bases, an index ϕ0, indicating a shifting of the frontier levels in respect to the balanced system is proposed. The nucleic bases are strictly divided into two groups: predominantly, donors are purine bases (ϕ0 > 0.5), and, preferably, acceptors are pyrimidine bases (ϕ0 < 0.5). The energies of the MO were evaluated both experimentally and quantum-chemically. Difference of the indices Δϕ0 is the ability of nitrogenous bases to form stable π-electronic complexes.